IN-HOSPITAL MORTALITY DESCRIPTION OF PATIENTS POST DECOMPRESSION TREPANATION AND EVACUATION OF INTRACEREBRAL HEMORRHAGE - Arisetijono, Eko; Agustin, Aisyiyah Alviana (MNJ (Malang Neurology Journal), 2025)
Background: In 2010, there were 33 million global stroke cases, with hemorrhagic stroke responsible for one-third of cases and over half of deaths. Intracerebral hemorrhage (ICH) is more common in low-income countries, the elderly, men, and African-Asian populations. Despite surgery aiming to reduce mortality, postoperative death rates remain high (22-62%), especially among elderly patients with hypertension. Objective: To determine the in-hospital mortality rate of patients following decompressive trepanation and evacuation of intracerebral hemorrhage at Saiful Anwar Hospital, East Java, from March 2023 to March 2024. Method: This is a retrospective descriptive study at Saiful Anwar Hospital, East Java, to identify the in-hospital mortality rate of patients who underwent decompressive trepanation and evacuation of intracerebral hemorrhage (March 2023-March 2024). Samples were taken from medical records of CVA ICH post-TDE ICH patients and analyzed using frequency, mean, median, and standard deviation. Results: The study at Saiful Anwar Regional General Hospital (March 2023-March 2024) involved 74 CVA ICH patients who underwent decompressive trepanation. Of these, 54% were male, 46% female, and the most common age group was 46-60 years (44.6%). Most patients were from Malang (75.67%), with 11 from Kedungkandang and 13 from Malang Timur. The mortality rate was 75.6%. Conclusion: A high mortality rate was observed in post-TDE ICH patients at Saiful Anwar Regional General Hospital, with respiratory failure complications being the main factor. Further research is needed to understand the risk factors for mortality. From this study, Artificial Intelligence can be developed to predict post-operative mortality.